التمكين الاجتماعي للمعاقين حركيا داخل الوسط الحضري بالجزائر - ميسه بوعلام; لعلام عبدالنور (University of Eloued جامعة الوادي, 2024)
Abstract: In this work, we study the social empowerment of physically handicapped individuals in Algerian cities, via exploring the reality that this category faces inside urban societies as the difficulties to adapt with the urban environment and sociological integration with other individuals. In addition, we present the fields that we should make the handicapped able to access inside urban societies and Algerian cities in order to decrease and tackle these obstacles. Social empowerment is presented in two parts: empowerment in internal spaces and empowerment inside external spaces of urban society. This empowerment makes physical handicapped totally and coherently integrated in all of its vital components. ملخص: يستهدف هذا المقال موضوع التمكين الاجتماعي للمعاقين حركيا في المدن الجزائرية وذلك من خلال تبيان الواقع الذي تعيشه هذه الفئات داخل الوسط الحضري من صعوبات في التكيف مع البيئة الحضرية واندماج اجتماعي مع الأفراد. وقدمت هذه الورقة كذلك المجالات التي يجب أن ي يُمَكَّنْ منها المعاق داخل الوسط الحضري والمدن الجزائرية لكي تقلل من هذه صعوبات التي يعيشها المعاق يوميا. وينقسم التمكين الاجتماعي للمعاقين حركيا على جزئين، تمكين داخل الفضاءات الداخلية للمسكن، وتمكين داخل الفضاءات الخارجية بالوسط الحضري. وهذا التمكين يؤدي إلى اندماج المعاقين حركيا اندماجا متكامل ومنسجم في جميع مكونات الحياتية له سوءا في الفضاء الداخلي أو الخارجي بالوسط الحضري.
Keywords: التمكين الاجتماعي; الوسط الحضري; المعاقين حركيا; social empowerment; motion disability; urban areas